Child labor and the transition between school and work - Akee, Randall K. Q.; Edmonds, Eric V., 1971-; Tatsiramos, Konstantinos (Research in labor economics ;, 2010)
More than 190 million children under 15 are working in the world today. Academic and policy research on child labor and related questions about how children spend their time in low income countries has boomed in recent years. This volume contains fresh knowledge to help better understand the relationship between child labor and the transition between school and work. It contains 11 original research papers by authors from Africa, Asia, Latin America as well as the United States and Europe. These papers offer insights and answers to issues such as: how to measure child labor; how the returns to education in the adult labor market affect children's school enrollment; how cash transfer programs affect schooling and children's participation in market and non-market activities; how child labor and schooling affect health; why children participate in activities that are labeled worst forms of child labor; how children's time is allocated along gender lines; what role local labor demand plays in shaping the work and schooling decisions of children; and how many hours of work can be undertaken before negative effects on school attendance are observed.